Status of Red Blood Cell Indices in Iron Deficiency Anemia and β Thalassaemia Trait: A Comparative Study - Mondal, Biva; Parvez, Mashud; Rana, Md Masud; Rahman, Lotifur; Zahan, Rowshan; Pal, Kishor Chandra; Khan, Waqer Ahmed (Dhaka Shishu (Children) Hospital Journal, 2022)
Background: Iron deficiency anemia (IDA) and b thalassemia trait (b -TT) are the two important differential diagnosis of microcytic hypochromic anaemia. It is important to distinguish between the above two conditions to avoid unnecessary iron therapy. Red blood cell (RBCs) indices are simple, easy, and cost effective method to get a primary and valuable information regarding the diagnosis of IDA and b -TT. Objectives: This study was aimed to compare the RBC count, hemoglobin (Hb), hematocrit (Hct%), RBC indices, mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH), mean corpuscular hemoglobin concentration (MCHC), red cell distribution width (RDW) and redcell distribution width index (RDWI) in Iron deficiency anemia and b thalassemia trait. Methods: This cross-sectional comparative study was conducted in the department of clinical pathology, Dhaka Shishu Hospital, Dhaka from July 2019 to March 2020. Total 107 patients with microcytic hypochromic anaemia (64 subjects of IDA and 43 subjects of b -TT were tested for RBC count, Hb%, MCV, MCH, MCHC, RDW, and PCV from venous blood by haematology analyser. Serum ferritin was measured by Enzyme Linked Immunosorbent Assays (ELISA). Statistical analysis was performed by SPSS version 22. Statistical significance was set at p value less than 0.05. Results: RBC count, Hb, and Hct,MCV, MCH and MCHC were significantly lower and RDW and RDWI was significantly higher in IDA group than in b- TT group (p< 0.001). Similar result was observed in male and female participants when compared them in separate group. Conclusion: The study showed that RBC count, Hb, Hct, MCV, MCH, and MCHC were significantly lower in IDA group than in b-TT group, whereas RDW and RDWI were significantly higher in IDA group than in b-TT group. DS (Child) H J 2021; 37(1): 9-14